THE CONCEPT OF EDUCATION CURRICULUM IN THE PERSPECTIVE OF ALI AHMAD MADZKUR - Indah Wahyu Ningsih; Atik Rosanti; Izuddin Musthafa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2022)
This study aims to describe the results of the study of the concept of the education curriculum in the perspective of the Minhajut Tarbiyah fii tashawuril Islamic book. The method used in this study uses alibrary research, that library research can be interpreted as a series of activities related to the methods of collecting library data, reading and recording and processing research materials. The results of this study indicate that basically the Islamic Education curriculum is a reflection of the knowledge paradigm according to Islam. Fundamentally includes two basic human needs, namely those oriented to material needs and oriented to spiritual needs. These two needs form the basis for the preparation of material in the Islamic education curriculum. It can be understood that educational curriculum material is always closely related to a number of theoretical and practical knowledge. Islamic education curriculum is very rich, this should be internalized in the overall projection of Islamic education. By relying on general projections of curriculum development, Islamic education materials will be dynamic in following and responding to developments in one aspect, also in other aspects always reflecting Islam as a religious teaching.